DETERMINACIÓN DE 222Rn POR ADSORCIÓN EN CARBÓN ACTIVADO Y SU IMPACTO RADIO AMBIENTAL EN DOS INSTITUCIONES EDUCATIVAS DEL DEPARTAMENTO DE PUNO (MACUSANI) - Chui, H. (2006)
An enemy of the health is invisible, frightful and quiet exists that appropriately is proliferated in closed environments. An inert gas denominated radon, which is product of uranium 238U, uranium 235U and thorium 232Th and is considered cancerigenic by the World Organization of the Health (WHO). By the abrupt climatic changes in the Puno zone (Macusani), the pupils of the schools are forced to study in closed rooms. Macusani is the most important district of Peru which produces uranium. Uranium disintegrates in its daughters 218Po, 214Pb, 214Bi, 214Po… 206Pb, which are radioactive and dangerous. For that reason the present work of investigation focuses on the calculation the concentration of radon, in educative environments and the impact that it generates on the students. This study was made in Macusani. The analysis (with techniques of gamma spectroscopy and canister of activated charcoal) was done with the support of the x-rays fluorescence in the laboratories of the Peruvian Institute of Nuclear Energy (IPEN) with technical support enabled by the IPEN area of Radiological Security.